Dissolution of lead- and lead-arsenic-jarosites at pH 2 and 8 and 20 C: Insights from batch experiments - Wright, Kathleen; Smith, A.; Dubbin, W.; Hudson-Edwards, K. (Elsevier Science BV, 2006)
Lead- and Pb-As-jarosites are minerals common to acidic, sulphate-rich environments, including weathering zones of sulphide ore deposits and acid rock or acid mine drainage (ARD/AMD) sites, and often form on or near galena. The structures of these jarosites are based on linear tetrahedral-octahedral-tetrahedral (T-O-T) sheets, comprised of slightly distorted FeO6 octahedra and SO4 2- (-AsO4 3- in Pb-As-jarosites) tetrahedra. To better understand the dissolution mechanisms and products of the break down of Pb- and Pb-As-jarosite, preliminary batch dissolution experiments were conducted on synthetic Pb- and Pb-As-jarosite at pH 2 and 20 C, to mimic environments affected by ARD/AMD, and at pH 8 and 20 C, to simulate ARD/AMD environments recently remediated with slaked lime (Ca(OH)2). All four dissolutions are incongruent. Dissolution of Pb-jarosite at pH 2 yields aqueous Pb, Fe and SO4 2-. The pH 8 Pb-jarosite dissolution yields aqueous Pb, SO4 2- and poorly crystalline Fe(OH)3, which does not appear to resorb Pb or SO4 2-, possibly due to the low solution pH (3.44-3.54) at the end of the experiment. The pH 2 and 8 dissolutions of Pb-As-jarosite result in the formation of secondary compounds (poorly crystalline PbSO4 for pH 2 dissolution; poorly crystalline PbSO4 and Fe(OH)3 for pH 8 dissolution), which may act as dissolution inhibitors after 250 to 300 h of dissolution. In the pH 2 dissolution, aqueous Fe, SO4 2- and AsO4 3- also form, and in the pH 8 dissolution, Fe(OH)3 precipitates then subsequently resorbs aqueous AsO4 3-. The dissolutions probably proceed by preferred dissolution of the A- and T-sites, which contain Pb, and SO4 2-and AsO4 3-, respectively, rather than Fe, which is sterically remote, within the T-O-T Pb- and Pb-As-jarosite structures.These data provide the foundation necessary for further, more detailed investigations into the dissolution of Pb- and Pb-As-jarosites.